Evaluasi Efisiensi Kerja Mesin Chopper dengan Integrasi Bagging Scale dan Conveyor pada Produksi Pakan Hijauan di Peternakan PT.X: Evaluation of Forage Feed Production and Work Posture After Chopper Machine Modification at PT. X Farm - Ridwan, Habibi; Apri Astuti, Dewi; Jakaria; Alexander, Kevin (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
Conventional chopper machines in farms such as PT. X often faces limitations in capacity and a lack of ergonomic design for operators. Modernization of the machine, including modifications in design and motor, is expected to improve production capacity and operator comfort. This study aims to assess the effect of chopper machine modification on improving production efficiency and operator ergonomics. Data was collected through direct field practice, observation, documentation, and interviews. The data obtained for evaluating machine capacity were analysed using the Paired T-Test, while comparative variables such as machine design, forage cutting percentage, and rapid entire body assessment (REBA) were analyzed descriptively. The results showed that modifications to the chopper machine at PT. X had a significant impact on increasing operational efficiency and reducing ergonomic risks for operators. Machine working capacity increased by 91.28%, from 1,079.32 kg hour-1 to 2,064.50 kg hour-1, accompanied by a reduction in total chopping cycle time from 66.79 seconds to 34.90 seconds. Although idle time slightly increased due to changes in the number of operators, work efficiency still showed substantial improvement through the integration of semi-automatic systems (bagging scale and conveyor). From an ergonomic perspective, posture analysis using the REBA method indicated a reduction in risk level from medium (score 7) before modification to low (score 3) after modification. In conclusion, modifications to the chopper machine at PT. X significantly increased operational efficiency, with a production capacity increase of up to 91.28% and a reduction in cycle time. Ergonomic evaluation showed a decrease in posture-related risk from medium to low. These findings demonstrate that the modifications not only accelerated the production process but also enhanced operator comfort and safety. Key words: bagging scales, chopper machine, conveyor, ergonomic evaluation, forage production